2020
DOI: 10.1530/vb-20-0007
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells on the move: dynamics in vascular morphogenesis and disease

Abstract: The vascular system is a hierarchically organized network of blood vessels that play crucial roles in embryogenesis, homeostasis and disease. Blood vessels are built by endothelial cells - the cells lining the interior of blood vessels, through a process named vascular morphogenesis. Endothelial cells react to different biomechanical signals in their environment by adjusting their behavior: a) invade, proliferate and fuse to form new vessels (angiogenesis); b) remodel, regress and establish hierarchy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 160 publications
(205 reference statements)
0
49
0
Order By: Relevance
“…Vascular endothelial growth factor (VEGF) signaling is a master regulator of tip cell biology, and it was shown to regulate endothelial tip cell invasion and sprouting angiogenesis ( 1 , 2 , 12 ). CDC42 and RAC1, downstream of VEGF, are master regulators of endothelial tip cell membrane protrusions ( 13 15 ).…”
mentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) signaling is a master regulator of tip cell biology, and it was shown to regulate endothelial tip cell invasion and sprouting angiogenesis ( 1 , 2 , 12 ). CDC42 and RAC1, downstream of VEGF, are master regulators of endothelial tip cell membrane protrusions ( 13 15 ).…”
mentioning
confidence: 99%
“…During blood vessel formation endothelial junctions play permissive as well as active roles, driving cell rearrangements and cell elongation while maintaining vascular integrity at the same time (Paatero et al, 2018; Sauteur et al, 2014; reviewed by Fonseca et al, 2020; Okuda and Hogan, 2020). Furthermore, endothelial junctions are thought to sense and transmit mechanical forces and thus regulate the collective endothelial response to changes in blood flow or pressure, which occur at the onset of blood flow in a newly formed vessel.…”
Section: Resultsmentioning
confidence: 99%
“…During vascular morphogenesis as well as in functional blood vessels, endothelial cells generate dynamic junctional protrusions, called junction-based lamellipodia (JBL) or junction-associated intermittent lamellipodia (JAIL), which have been observed in different vascular beds of zebrafish embryo as well as mouse embryos and the postnatal retina (reviewed by Cao and Schnittler, 2019; Fonseca et al, 2020). Live-imaging of JBL in zebrafish embryos showed that they are highly dynamic oscillatory structures and are associated with cell movements within the endothelium (Paatero et al, 2018; reviewed by Okuda and Hogan, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis, defined as the formation of new capillaries from pre-existing blood vessels, is an essential physiological process involved in wound healing, ovulation, vascular and embryonic development [1]. It is a complex process characterized by the migration of endothelial tip and stalk cells in response to a variety of stimuli including chemokines and growth factors such as VEGFA, and is regulated by a variety of signaling pathways [2]. Disordered angiogenesis stimulates a wide range of pathophysiological conditions such as ischemic circulatory disease, cancer, chronic inflammation, atherosclerosis, arthritis and diabetic retinopathy [3].…”
Section: Introductionmentioning
confidence: 99%